Analysis of Assessment Results of Cerebral Palsy Children with Barriers to Complex Communication Needs - Rahmatul Janah; Andri Eliyas; Imas Diana Aprilia; Riksma Nurahmi Rinalti Akhlan; Budi Susetyo (Edumaspul: Jurnal Pendidikan, 2023)
This study describes the analysis of assessment results in cerebral palsy children with barriers to complex communication needs. The assessment used is a developmental assessment on motor, cognitive, and language aspects. The research was conducted using qualitative descriptive research. Based on the results of assessments conducted on cerebral palsy children with complex communication needs barriers, a child profile related to the child's potential, obstacles, and needs can be formulated. Where the child's profile is useful for designing communication programs for complex communication needs children so that it can help them communicate both using expressive language and receptive language. Keywords: analysis of assessment results, cerebral palsy, complex communication needs